Law and society in Vietnam / Mark Sidel. - Sidel, Mark (Cambridge studies in law and society., 2008)
This book is a unique analysis of the struggle to build a rule of law in one of the world's most dynamic and vibrant nations - a socialist state that is seeking to build a market economy while struggling to pursue an ethos of social equality and opportunity. It addresses constitutional change, the assertion of constitutional claims by citizens, the formation of a strong civil society and non-profit sector, the emergence of economic law and the battles over who is benefited by the economic regulation, labor law and the protection of migrant and export labor, the rise of lawyers and public interest law, and other key topics. Alongside other countries, comparisons are made to parallel developments in another transforming socialist state, the People's Republic of China.